Sundanese Kinship Terminology in an Old Sundanese Manuscript: Saá¹…hyaá¹… Siksakanda á¹„ KarÄ•sian (1518 AD) - Mulyanto, Dede - (Komunitas, 2019)
This article is attempted to reconstruct Sundanese kinship terminology from an Old Sundanese manuscript: Saá¹…hyaá¹… Sikakanda á¹… KarÄ•sian (The Godly Guidelines to the Righteousness, 1518 AD). In this manuscript, there are 26 kin term of references for 23 kin categories. Basically, Old Sundanese kinship terminology have strong characteristics toward lineal-Eskimo type in which terms of reference for members of nuclear family more descriptive than for other relatives outside it. Balance term distributions for collateral relatives also important in this type. Comparing with modern Sundanese, there are no structural change in Sundanese kinship terminology.